Melatonin and derived l-tryptophan metabolites produced during alcoholic fermentation by different wine yeast strains. (15th February 2017) - Fernández-Cruz, E.; Álvarez-Fernández, M.A.; Valero, E.; Troncoso, A.M.; García-Parrilla, M.C.
Highlights: Melatonin is synthesised by non- Saccharomyces strains. Red Fruit strain produces more melatonin than others included in this study. Non- Saccharomyces synthesised Tryptophan ethyl ester during the fermentation process. Melatonin synthesis took place at end of the exponential growth phase. Saccharomyces strains consumed Tryptophan faster than non- Saccharomyces . Abstract: Melatonin is a neurohormone involved in the regulation of circadian rhythms in humans. Evidence has recently been found of its occurrence in wines and its role in the winemaking process. The yeast Saccharomyces cerevisiae is consequently thought to be important in Melatonin synthesis, but limited data and reference texts are available on this synthetic pathway. This paper aims to elucidate whether the synthetic pathway of Melatonin in Saccharomyces and non-Saccharomyces strains involves these intermediates. To this end, seven commercial strains comprising Saccharomyces cerevisiae (Red Fruit, ES488, Lalvin QA23, Uvaferm BC, and Lalvin ICV GRE) and non-Saccharomyces ( Torulaspora delbrueckii and Metschnikowia pulcherrima ) were monitored, under controlled fermentation conditions, in synthetic must, for seven days. Samples were analysed using a UHPLC—HRMS system (Qexactive). Five out of the seven strains formed Melatonin during the fermentation process: three S. cerevisiae strains and the two non-Saccharomyces. Additionally, other compounds derived froml -tryptophan occurred during fermentation.